Analisis Dinamika Stroller (Kereta Bayi) dengan Metode Port-Controlled Hamiltonian System (PCHS) berbasis Komputasi Fisika - Ariska, Melly; Akhsan, Hamdi; Muslim, Muhammad (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2020)
Computational physics can be used to help solve complex dynamics equations, both translational and rotational. The purpose of this study is to obtain differences in the dynamics of mechanical systems with non-holonomic constraints in various flat and curved configuration spaces based on physics computing. In this study the reduction used is a mathematical calculation of the Port-Contolled Hamiltonian System (PCHS) equation in a mechanical system that is a Stroller, so that the equation used in determining the Stroller motion equation with and without friction that moves in the curved plane in the form of a spherical surface with various initial conditions based on maple is Poincaré's equation which is based on Routhian reduction with and without friction. The effect of friction can be clearly seen through dynamics and graphical equations on the Stroller. This method can reduce the Stroller motion equation with and without friction that moves on the ball sphere clearly in the form of a set of differential equations. The findings of this study are dynamic equations and graphs of Stroller equations with and without friction that move in the curved plane in the form of a spherical ball with varying initial conditions based on maples. This study proves physical concepts about dynamics and kinematics and analyzes Stroller dynamics using computational physics to determine the characteristics of complex and complex Stroller movements, both translational and rotational.